2020
DOI: 10.21831/jpe.v8i1.30618
|View full text |Cite
|
Sign up to set email alerts
|

Project-based learning to improve scientific literacy for primary education postgraduate students in science subject

Abstract: The research aimed to describe the learning activities and the ability of scientific literacy (attitude, context, knowledge, and competence) Students of Primary Education Postgraduate Program of Bengkulu University in natural science subjects by using the PjBL model. The Classroom Action Research done in three cycles for Primary Education Postgraduate Program students of Bengkulu University in the first semester of 2019/2020 academic year. Instrument and data collection techniques are observations, tests, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…This result showed that enhancing Student Activity Sheets based on Scientific and Problem Based Learning (PBL) in the Introduction to Microeconomics course has opportunity to increase the student's motivation to solve the problem and increase student achievement exponentially. This study in line with previous study of Winarni (2020) that found that that the use of Student Worksheets could encourage students to: have meaningful knowledge, (b) enjoy Data Analysis courses and the learning methods it uses, be motivated to learn and solve problems and projects in Student Worksheets independently, be active during lectures. The average student who has not completed has not been able to answer questions regarding Opportunity cost or opportunity costs and economic problems.…”
Section: Design Of Trialsupporting
confidence: 90%
See 1 more Smart Citation
“…This result showed that enhancing Student Activity Sheets based on Scientific and Problem Based Learning (PBL) in the Introduction to Microeconomics course has opportunity to increase the student's motivation to solve the problem and increase student achievement exponentially. This study in line with previous study of Winarni (2020) that found that that the use of Student Worksheets could encourage students to: have meaningful knowledge, (b) enjoy Data Analysis courses and the learning methods it uses, be motivated to learn and solve problems and projects in Student Worksheets independently, be active during lectures. The average student who has not completed has not been able to answer questions regarding Opportunity cost or opportunity costs and economic problems.…”
Section: Design Of Trialsupporting
confidence: 90%
“…Krisdiana, et al (2019) in their research stated that the development of Student Worksheets was valid and practical for use in mathematical statistics courses. Furthermore, Djalal, et al (2017) stated that the development of Problem-Based Algebraic LKM to Optimize Mathematical Reasoning Ability of Mathematics Education Students was in the good category and was suitable for use, and Winarni (2020) based on his research, stated that the implementation results showed that the use of Student Worksheets could encourage students to: have meaningful knowledge, (b) enjoy Data Analysis courses and the learning methods it uses, be motivated to learn and solve problems and projects in Student Worksheets independently, be active during lectures.…”
Section: Introductionmentioning
confidence: 99%
“…The instruments used are HOTS tests and rubrics. The indicators of the success of the action are the activities of lecturers and students in the teaching and learning process using PjBL in the excellent category and the percentage of students who demonstrate the attitude, context, knowledge, and competence of science fulfill the excellent category of at least 80% (Winarni & Purwandari, 2020).…”
Section: Aspectmentioning
confidence: 99%
“…Science is a branch of science that studies all natural phenomena in the form of facts, concepts, and principles which are proven through scientific processes. Science is a collection of knowledge obtained by observations of natural phenomena, then systematically arranged to solve problems in daily life [11]. It is better to involve students in various domains in science learning, namely knowledge, attitudes, context, and multiple competencies, to find knowledge used in problem-solving in their environment.…”
Section: Health Literacymentioning
confidence: 99%